(untitled) (Research, Society and Development, 2025)
Global dependence on fossil fuels has generated significant environmental consequences, such as increased greenhouse gas emissions, air pollution and climate change. In response to these challenges, there is growing interest in alternative energy sources that are more sustainable and less harmful to the environment. Hydrogen appears as a promising alternative due to its high energy capacity and the fact that its direct combustion generates only water as a by-product, without emission of atmospheric pollutants. The aim of this article is to explore the feasibility and benefits of bacterial anaerobic fermentation as an effective strategy for hydrogen production. Literature data highlights that this approach not only provides a clean energy source, but also contributes to sustainable waste management. This type of fermentation offers an economical and accessible alternative to hydrogen production, using organic waste by-products from industrial or agricultural activities, reducing production costs and reducing environmental impacts. The study addressed the theoretical and practical foundations of this technology, its challenges and opportunities, and how it can be integrated into broader strategies for a more sustainable energy future.